Analisis Keaktifan Siswa Kelas IV Pada Pembelajaran IPA di SD Swasta Muhammadiyah 25 Medan - Adek Kesuma Ningrum; Yuli Amalia Hutajulu; Indah Pratiwi (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
Abstract Science learning is currently still focused on children’s ability to remember information without connecting it with everyday life, so that the learning process is less effective in being able to stimulate student activity during learning. Therefore this study aims to analyze the activity of fourth grade student at SDS Muhammadiyah 25 Medan in learning natural science. This research was conducted on may 13, 2023, the subjects of this study were 10 fourth grade students. Based on the result of the questionnaire percentage of students’ activeness in science learning is in the “Average” criterion because it is under the indicator of success in learning activeness, namely in the very good criterion with a percentage of 80% -100%. Abstrak. Pembelajaran IPA saat ini masih berfokus pada kemampuan anak dalam mengingat informasi tanpa menghubungkan dengan kehidupan sehari-hari, sehingga proses pembelajaran kurang efektif untuk dapat menstimulus keaktifan siswa pada saat pembelajaran. Maka dari itu penelitian ini bertujuan untuk menganalisis keaktifan siswa kelas IV SDS Muhammadiyah 25 Medan pada pembelajaran IPA. Penelitian ini dilakukan pada tanggal 13 Mei 2023, subyek penelitian ini adalah siswa kelas IV sebanyak 10 responden. Berdasarkan hasil presentase angket keaktifan siswa dalam pembelajaran IPA berada pada kriteria “Cukup” karena berada dibawah indikator keberhasilan keaktifan belajar yaitu pada kriteria Sangat baik dengan persentase sebesar 80%-100%. Kata Kunci: Keaktifan siswa, Pembelajaran IPA, Sekolah Dasar.